Novel pH-sensitive catechol dyes synthesised by a three component one-pot reaction - Calmels, Juan José; Aguilar, Leandro; Mancebo-Aracil, Juan; Radivoy, Gabriel; Domini, Claudia; Garrido, Mariano; Sánchez, Miguel D.; Nador, Fabiana (Frontiers in Chemistry, 2023)
The synthesis and characterisation of new dyes based on indolizines bearing catechol groups in their structure is presented. The preparation was carried out through a simple three component one-pot reaction promoted by CuNPs/C, between pyridine-2-carbaldehyde, an aromatic alkyne and a tetrahydroisoquinoline (THIQ) functionalized with catechol groups. The products were isolated in 30-34% yield, which was considered more than acceptable considering that the catechol hydroxyl groups were not protected prior to reaction. In view of the colour developed by the products and their response to the acidic and basic conditions of the medium, product 3aa was studied by UV-Vis and NMR spectroscopies at different pH values. We concluded that product 3aa suffered two deprotonations at pKa of 4.4 and 9.5, giving three species in a pH range between 2-12, with colours varying from light red to deep orange. The reversibility of the process observed for 3aa at different pH values, together with its changes in colour, make this new family of products attractive candidates to use them as pH indicators.